Four Times Peter : Portrayals of Peter in the Four Gospels and at Philippi - Cassidy, Richard J. (Book collections on Project MUSE., 2007)
Because he plays such a prominent role in the New Testament and the tradition of the church, the apostle Peter has been the focus of much scholarship over the centuries. One wonders whether there can be anything more to say about Peter. Indeed, there is. In Four Times Peter Richard Cassidy takes a narrative critical look at Peter in the story of each gospel individually (rather than studying Peter via a side-by-side analysis of the gospels). Cassidy looks first to the character of Jesus in each of the gospels and then to the group of apostles as a whole before turning to Peter. In the end, Four Times Peter allows an intriguing portrait of this apostle to emerge. Readers discover a portrait of Peter that would have been familiar to the earliest Christian communities. And it is this ancient portrait that gives modern readers a refreshing new sense of Peter. Richard J. Cassidy, STL, PhD, is Professor of Sacred Scripture at Sacred Heart Major Seminary, Detroit, Michigan. This book is part of the series Interfaces.